2018
DOI: 10.1007/s10549-018-4901-0
|View full text |Cite
|
Sign up to set email alerts
|

CDK4/6 inhibitors in advanced hormone receptor-positive/HER2-negative breast cancer: a systematic review and meta-analysis of randomized trials

Abstract: Emerging data provide a new standard treatment for advanced HR+/HER2- breast cancer, regardless of menopausal status, prior hormonal/chemotherapy treatments delivered, sites of metastasis. However, benefits should be balanced with longer treatment duration, toxicities, and costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 33 publications
1
54
0
4
Order By: Relevance
“…This behavior relies on the diffused perception, among both oncologists and patients, that chemotherapy is a more potent treatment, yielding on average a higher ORR than ET-based treatments. In contrast, our meta-analysis, as well as the previous ones [56][57][58][59] confirms that the combination of CDK4/6 inhibitors and ET yields a very high rate of tumour regression, which is on average as high as 55% for patients with measurable disease, with no heterogeneity among different compounds. To the best of our knowledge, this ORR is higher than we would expect with mono-chemotherapy and comparable (but still lower) to what we would expect with an aggressive polychemotherapy in HR+ patient populations.…”
Section: Discussionsupporting
confidence: 74%
“…This behavior relies on the diffused perception, among both oncologists and patients, that chemotherapy is a more potent treatment, yielding on average a higher ORR than ET-based treatments. In contrast, our meta-analysis, as well as the previous ones [56][57][58][59] confirms that the combination of CDK4/6 inhibitors and ET yields a very high rate of tumour regression, which is on average as high as 55% for patients with measurable disease, with no heterogeneity among different compounds. To the best of our knowledge, this ORR is higher than we would expect with mono-chemotherapy and comparable (but still lower) to what we would expect with an aggressive polychemotherapy in HR+ patient populations.…”
Section: Discussionsupporting
confidence: 74%
“…Several other previously published meta-analyses and pooled analyses of PFS concluded that the use of CDK4/6 inhibitors plus ET was associated with significantly extended PFS. 2,3,13,19 The survival data, references, and subgroup analyses included in the present meta-analysis are more comprehensive, complete, and contain a larger sample size compared with those previously published meta-analyses. Thus, the present meta-analysis has several strengths over previous analyses.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of CDK4/6 inhibitors to treatment regimens was associated with a high risk of increased rates of neutropenia, leukopenia, and diarrhea, 3 grade 3/4 AEs that should be considered when treatment periods are long. 2 Neutropenia, leukopenia, and diarrhea were the most common symptoms observed among patients who received CDK4/6 inhibitors plus ET treatment of metastatic breast cancer, with diarrhea being the most frequent nonhematologic grade 3/4 AE. 36,39 However, those grade 3/4 AEs may be controlled through experience, medication, or dose Downloaded From: https://jamanetwork.com/ on 10/31/2020 adjustment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations